Alpha-Fetoprotein Binding Mucin and Scavenger Receptors: An Available Bio-Target for Treating Cancer - Lin, Bo; Wang, Qiujiao; Liu, Kun; Dong, Xu; Zhu, Mingyue; Li, Mengsen (Frontiers in Oncology, 2021)
Alpha-fetoprotein (AFP) entrance into cancer cells is mediated by AFP receptors (AFPRs) and exerts malignant effects. Therefore, understanding the structure of AFPRs will facilitate the development of rational approaches for vacine design, drug delivery, antagonizing immune suppression and diagnostic imaging to treat cancer effectively. Throughout the last three decades, the identification of universal receptors for AFP has failed due to their complex carbohydrate polymer structures. Here, we focused on the two types of binding proteins or receptors that may serve as AFPRs, namely, the A) mucin receptors family, and B) the scavenger family. We presented an informative review with detailed descriptions of the signal transduction, cross-talk, and interplay of various transcription factors which highlight the downstream events following AFP binding to mucin or scavenger receptors. We mainly explored the underlying mechanisms involved mucin or scavenger receptors that interact with AFP, provide more evidence to support these receptors as tumor AFPRs, and establish a theoretical basis for targeting therapy of cancer.